PENGARUH PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP PEROLEHAN BELAJAR IPS DI SD - Mulyana, Mulyana; Marzuki, Marzuki; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze the effect of cooperative learning type numbered heads together toward the acquisition of learning social science class in elementary school the country V 14 South Pontianak. This research uses experimental methods with Pre-Experimental Design types of One Group Pretest – Posttest Design. The population of the entire grade V SDN 14 South Pontianak which consists of 35 students, sampling is a non probability sampling convenience sampling type i.e. the whole grade V SDN 14 South Pontianak. The techniques used in data collection is a measurement tool collecting data used is the objective form of the written test. Based on the analysis of data obtained average results pre-test students 58.79 and results the average post-test students 72.50. After a test of t obtained thitung of 8.61 with db = 35-1 = 34 with degrees of significant (α) = 5% obtained ttabel of 1.6918, turns thitung ttabel ≥ or ≥ 8.61 1.6918 which means there is a significant influence on the application of learning cooperative type numbered heads together. From the results of the calculation of effect size (ES), retrieved the ES of 0.77 criteria belongs to. This means learning cooperative type numbered heads together provide positive influence towards obtaining studied Social Science at grade V SDN 14 South Pontianak. Keywords : Numbered Head Together, The Acquisition , Learning Social Science